Teacher Professionalism in Elementary School During The Adaptation of New Habits - Slamet Supriono (JP2D (Jurnal Penelitian Pendidikan Dasar) UNTAN, 2022)
Teacher professionalism must always be maintained and improved on an ongoing basis to be able to create superior students and a conducive learning situation, hence the need for research that will be used as a standard of measurement, especially at this time the adaptation of new habits is very problematic both for the teachers themselves and for others student. This research method was a quantitative descriptive study. “Descriptive research is intended to describe a situation or phenomena as they are. Survey research was conducted to make generalizations from observation, and the results will be more accurate. The survey method was used to obtain data from certain natural (not artificial) places, but researchers carry out treatments in data collection, for example, by giving a questionnaire using a total sampling technique, all teachers are used as direct objects in data collection and with the results of the study answering yes 874 with a percentage of 95% and 46 answered no with a percentage of 5% meaning that the professionalism of the teacher when carrying out the task was classified as good and very good because he was still able and able to carry out his duties according to the model, strategy and approach to students and between teachers while at school.